The Legal Protection of The Child's Right of Obtaining the Nationality Through the Order 05-01 the Amended and Complemented to The Order 70-86 That Includes the Nationality Law - Amara, Amara (Journal of Legal Studies and Researches, 2021)
The right of obtaining the nationality for children is protected by Legislatives because it relates the child with his country through the amended order 05-01 of the Nationality Law. This includes the right of the child to obtain the nationality of his Algerian mother without any condition.